Effectiveness of Guided Inquiry-Based Worksheets in Improving Science Process Skills on Vibrations and Waves Material - Ira Nofita Sari; Lia Angraeni; Dedeh Kurniasih; Nurussaniah Nurussaniah (Universitas Hamzanwadi, 2024)
Science education is a key factor in developing students' science process skills and understanding of scientific concepts. Mastery of science process skills is one of the important ways to gain knowledge. By implementing Student Worksheets based on guided inquiry, science process skills and understanding of scientific concepts can be improved. This study examines the effect of guided inquiry-based worksheets on science process skills. This study used a quasi-experimental design with a one-group pretest-posttest model to examine the effectiveness of guided inquiry-based worksheets in improving students' science process skills on vibration and wave material. The research participants consisted of students enrolled in vibration and wave courses in the third semester of the Physics Education Study Program, Universitas PGRI Pontianak, who were selected using saturated sampling techniques. The instruments used in this study were science process skills tests in the form of pretests and posttests and science process skills observation sheets during learning which included observing, classifying, measuring, interpreting data, making hypotheses, designing experiments, conducting experiments, communicating, results, concluding, identifying variables, and using tools and materials. The data obtained were analyzed using paired t-test and N-Gain analysis. Based on the data obtained, both from pretest, posttest, and observation, it can be concluded that the use of guided inquiry-based worksheets is effective in improving students' science process skills in vibration and wave material. This increase is clearly seen in the pretest and posttest scores, as well as in the observation of skills that show positive developments in all indicators of science process skills.